The Long Non-Coding BC200 Is a Novel Circulating Biomarker of Parathyroid Carcinoma - Morotti, Annamaria; Cetani, Filomena; Passoni, Giulia; Borsari, Simona; Pardi, Elena; Guarnieri, Vito; Verdelli, Chiara; Tavanti, Giulia Stefania; Valenti, Luca; Bianco, Cristiana; Ferrero, Stefano; Corbetta, Sabrina; et al. (Frontiers in Endocrinology, 2022)
Long non-coding RNAs (lncRNAs) are an important class of epigenetic regulators involved in both physiological processes and cancer development. Preliminary evidence suggested that lncRNAs could act as accurate prognostic and diagnostic biomarkers. Parathyroid cancer is a rare endocrine neoplasia, whose management represents a clinical challenge due to the lack of accurate molecular biomarkers. Our previous findings showed that human parathyroid tumors are characterized by a different lncRNAs signature, suggesting heterogeneity through the different histotypes. Particularly, we found that the lncRNA BC200/BCYRN1 could represent a candidate biomarker for parathyroid carcinomas (PCas). Here we aimed to extend our preliminary data evaluating whether BC200 could be an accurate non-invasive biomarker of PCas to support the clinical management of patients affected by parathyroid tumors at diagnosis, prognosis and follow-up. To provide a non-invasive point-of-care for parathyroid carcinoma diagnosis and follow-up, we analyzed BC200 expression in patients’ serum through digital PCR. Our results show that BC200 counts are higher in serum from patients harboring PCa (n=4) compared to patients with parathyroid adenoma (PAd; n=27). Further, in PAd patients circulating BC200 levels are positively correlated with serum total calcium. Then, we found that BC200 is overexpressed in metastatic PCas (n=4) compared to non-metastatic ones (n=9). Finally, the lncRNA expression in PCa patients’ serum drops are reduced after parathyroidectomy, suggesting its possible use in the post-operative setting for patients' follow-up. Overall, these findings extend the knowledge on BC200 in parathyroid tumors, supporting its role as a useful biomarker for management of PCa.